Compact miniaturized antenna design and development for a leadless cardiac pacemaker - Abdelmouttalib Bousrout; Asma Khabba; Saida Ibnyaich; Tomader Mazri; Mohamed Habibi; Tole Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
Biomedical antennas play a crucial role in implantable medical telemetry, improving patient monitoring and overall well-being. This study presents a compact antenna designed for a lead-free pacemaker, with dimensions of 3.3×4×0.5 mm³. Miniaturization required open cuts in the ground plane and radiating patch, as well as a localized resistance element. The antenna features an exceptional bandwidth of 1646.8 MHz (1.0602-2.7070) GHz, guaranteeing constant performance in the human body. It covers the industrial, scientific and medical bands (ISM, 2.4-2.48 GHz) and ultra-high frequencies (UHF, 0.3-13 GHz). Simulation in a phantom produced a gain of -19.78 dBi at 2.45 GHz and -34.44 dBi at 1.2 GHz. Safety was confirmed by a specific absorption rate (SAR) study using a cardiac model. The antenna’s low SAR (10 g-Avg) enabled maximum input powers to be established: 20.2 mW at 1.2 GHz and 21.23 mW at 2.45 GHz. Comparative simulations using high-frequency structure simulator (HFSS) and computer simulation technology (CST) highlighted the antenna’s superiority over recent systems, demonstrating its effectiveness in the human heart. This antenna represents an advanced solution for improving patient care. Consequently, this antenna emerges as an advanced solution for addressing infectious diseases and cardiovascular conditions in the realm of medical advancements.